Penerapan Model Pembelajaran berbasis Masalah Berbantuan Aplikasi Geogebra Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Transformasi Geometri Kelas XI IPAS – 1 SMA Negeri 7 Medan - Agma Sukenti (Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this study was to find out how the strategy for implementing the Geogebra Application-assisted Problem-Based Learning Model (PBM) in improving student learning outcomes after applying the Geogebra Application-assisted Problem-Based Learning Model (PBM) on geometry transformation material in class XI IPS-1 SMA Negeri 7 Medan T.A. 2022/2023. This type of research is classroom action research (CAR) which is carried out in 2 cycles, each of which is held in 3 meetings. The subjects in this study were students of class XI IPS-1 SMA Negeri 7 Medan T.A. 2022/2023, totaling 35 people and objects in this study are student learning outcomes in the Geogebra Transformation material using the Problem-Based Learning Model (PBM) assisted by the Geogebra application. The research instruments used were observation and tests. From the results of data analysis from cycle 1 to cycle 2, student learning outcomes increased. At the time of the initial test in cycle I, the percentage of student learning completeness was (54%) with an average score (60%) with the number of students who completed 19 people and students unfinished 16 people or (46%). Whereas in cycle II the class average value reached 79% with a completeness level of 91%. Thus it can be concluded that the application of the Problem-Based Learning Model (PBM assisted by the Geogebra application in improving student learning outcomes in the geometry transformation material in class XI IPS-1 SMA Negeri 7 Medan T.A. 2022/2023. Suggestions that can be submitted from this study is that teachers should use The Problem-Based Learning Model (PBM) is assisted by the Geogebra Transformation Geometry application or other materials so that learning becomes more interesting and fun so that students are more active in learning activities. Keywords: Geogebra application, problem-based learning model, learning outcomes, geometry transformation